Expanding frontiers of cerebrovascular disease - Hachinski, Vladimir (Henry Stewart Talks, 2019)
Increasing numbers and DALY’s, Common risk and protective factors of stroke and dementia, Commonest outcome of cerebrovascular disease is vascular cognitive impairment, Identifying the treatable component of dementia, The Hachinski Ischemic Score, The two in one cerebral circulation, Vascular and neurodegenerative mechanisms meet at the neurovascular unit